El concepto de historia en walter benjamin: el desencantamiento de la idea de progreso (2020)
The text, On the Concept of History, written in XVIII fragments and two appendices, develops Benjamin's reflections around the theme of history where several categories emerge: historicism, historical materialism, messianism, current time, progress, continuity. It has, at first sight, a background that Benjamin's commentators insist on: the sacred and the profane, where these two categories are mixed, intertwined, dialectically interpenetrated. We could approach Walter's thought in his writing from the following thesis: historical materialism unveils the true history behind the illusion of progress, either as philosophical messianism or as enlightened revolution, where another look at time and space lies, where precisely the victims, the silenced of history, appear. Walter Benjamin's theses on the concept of history proclaim a disenchantment with the enlightened idea of progress. Concepts such as "weak messianic force" and "commemoration" are concepts that are repeatedly insisted upon as the basis for Benjamin's reading of another way of seeing the philosophy of history.